Pelatihan Asesmen Praktik Musik di MGMP SMP Seni Budaya Kabupaten Bengkayang - Yudhistira Oscar Olendo; Imam Ghozali; Zakarias Aria Widyatama Putra (Politeknik Negeri Cilacap, 2023)
Music practice assessment training at the Bengkayang Regency Arts and Culture Subject Teachers' Meeting is important considering the lack of development of assessments specifically in arts and culture learning. Objectivity when assessing a student's skill in practicing music needs to be evaluated. This form of evaluation can be done through an assessment of music practice. The PKM implementation method has stages, namely the preparation stage by coordinating with partners, the implementation stage conveying assessment material along with discussions and questions and answers, and the evaluation stage adjusting the results of activities in the form of rubrics that are worked on by participants with the conditions and situations of partner schools. The results obtained in this PKM are that participants have an objective view of the assessment of music practice and have an assessment rubric in determining the score of each music practice assessment criterion. With evaluation, it will continue to develop the assessment of the music. Through the Tanjungpura University Community Service program as well as the MGMP for Cultural Arts and also the Bengkayang Regency Education Office, the results of collaboration and friendship between implementers and partners have been.